A proof of a conjecture about a symmetric system of orthogonal polynomials. Issue 4 (2nd April 2020) - Castillo, K.; de Jesus, M. N.; Petronilho, J.
ABSTRACT: The purpose of this note is to give an affirmative answer to a conjecture appearing in Berg [Open problems. Integral Transforms Spec Funct. 2015;26(2):90–95].